Thermodynamics of certain refractory compounds. - Schick, Harold L. (Academic Press, 1966)
Thermodynamics of Certain Refractory Compounds, Volume II: Thermodynamic Tables, Bibliography, and Property File provides information pertinent to thermodynamics as a significant theoretical tool for predicting the chemical and physical behavior of materials under diverse environmental conditions. This book presents a compilation of thermodynamic tables generated on this project. Organized into three chapters, this volume begins with an overview of the wide range in quality of thermodynamic data. This text then presents a bibliography as well as property file, which is essentially a subject in.